Electability salience can bias voting decisions. (20th February 2023) - Minozzi, William; Woon, Jonathan
"Electability" received considerable attention during the 2020 Democratic primary campaign, with some critics claiming that the term was code for sexism. From a rational choice perspective, "electability" could affect voting in multiple ways, including via expected utility; previous scholarship suggests that many voters consider it as such. Yet this scholarship ignores the role that salience plays in decision making, and is silent on which sorts of candidate might benefit from the effects of priming electability. To address these issues, we conducted a survey experiment during the 2020 primary season, measuring Democratic primary voters' preferences for candidates, electability estimates, and candidate rankings. Our experiment manipulated salience by randomizing the order in which preferences and electability were elicited. We show that electability salience caused a substantial increase in the probability that a respondent made decisions based only on electability.